Optimization and implementation of a new methodology for washing glass bottles in a pharmaceutical industry - Pérez, Frank A. (2018)
The present study has the following objective: to design, implement and optimize a new method of washing glass bottles for the packaging of non-sterile liquid dosage forms, in a way that is a continuous process and in line with the packaging of this type of products. To carry out this new methodology was enabled in the equipment of glass bottle washing, as one of the improvements, a hot soft water inlet for the sanitization. This allowed us that within the washing sequence prior to its rinsing with purified water, placing a station where the bottles are sanitized with warm and soft water. To demonstrate that the new method of glass bottle washing is effective in eliminating viable and non-viable contaminants, as well as demonstrating that the physical and physicochemical properties of the products that are packaged in this bottles are not altered, tests were performed based in risk analysis. Based on this evaluation, the worst case glass bottle volume was determined in order to determine the waiting time of bottles before the packaging process and the product to be packed in the same for the purpose of sending it to studies of Stability and prove that the change does not impact on the quality attributes of the products that will be packaged in this type of bottles. The tests carried out: physical, physicochemical and microbiological at initial time, applying the new methodology designed, were compliant both for glass bottles without product and for glass bottles with product. The study includes as an advantages: optimization of the washing process, reduction of process times, improvement of productivity, increase of the installed capacity of the pharmaceutical plant of non-sterile liquids and generation of a positive economic impact.